Evolution of Vortex Structures Generated by a Rigid Flapping Wing with a Winglet in Quiescent Water - Srikanth Goli; Arnab Roy; Subhransu Roy; Imil Hamda Imran (Proceedings of Engineering and Technology Innovation, 2024)
This study aims to the utilization of vortex structures generated through wing flapping for achieving sustainable flight, and the motivation is elicited by the phenomenon observed in natural flyers. The vortex structures in the flow field generated by a flapping rigid wing are captured using vorticity and the LAMDA2 criterion. The study investigates a comparative analysis between a wing both with and without a winglet. Moreover, the influence of flapping frequency is examined as well. For the experiments, particle image velocimetry (PIV) measurements are employed for the flow field around mechanical flapping motion in a quiescent water condition. The flapping mechanism has one-degree freedom, showing a 1:3 ratio in motion, and tested wings at 1.5 and 2.0 Hz. A “modified” vortex filamentation and fragmentation phenomenon is proposed as a significant finding in the present study, based on a comprehensive analysis of the flow field around the wing with a winglet.